Occupational exposure to organic solvents : effects on human reproduction (The Hague, 2008)
"It is estimated that half a million workers in the Netherlands are regularly exposed to organic solvents. Some examples of well-known solvents are toluene, styrene, xylene, benzene and turpentine. These are widely used for degreasing and diluting, and are found in such products as ordinary paints, car paints, stains, and glues. Solvents evaporate, so those who work with these products tend to inhale them. It is known for a long time that inhaling organic solvent fumes may impair people’s health. In recent years, occupational exposure to these solvents has been linked to various effects. The most well-known and best documented effect is the occurrence of chronic toxic encephalopathy (CTE), also known as organic psycho syndrome (OPS). This involves serious damage to the nervous system, resulting in memory disorders, impaired concentration, mental inertia, fatigue, headache, irritability and depression. In addition, it is known that exposure to certain organic solvents (such as benzene) can cause cancer. Less is known about possible effects on reproduction. In 1999, that topic was at the centre of a commotion, following the publication of a Dutch study in men who had been examined at a fertility clinic. This study found that exposure to organic solvents appeared to be linked to reduced sperm quality. The results of this study led to questions being asked in the Dutch parliament. The results of another Dutch study were published in 2005. These results suggested that exposure to solvents might cause birth defects among the children of professional painters. ..."